Implementasi Standard Operational Procedure (Sop) Terhadap Kinerja Karyawan Di Industri Perbankan ( Study Kasus Bank Bri Unit Otista ) - Rukmana, Febi Indriyanti; Khudori, M.Heri; ., Zaharuddin; Suryati, Adelina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Employee performance is a critical factor supporting organizational success. The success or failure of an employee is contingent upon adherence to standards that gauge their work and evaluation within the supervisory framework established by the company. This study aimed to assess the impact of standard operating procedures and supervision on the performance of employees at Bank BRI Unit Otista. Employing a quantitative research method with an explanatory approach, data were gathered through a questionnaire. The study revealed a substantial influence of standard operating procedures on employee performance, with supervision also exhibiting a significant impact. Moreover, the combined effect of standard operating procedures and supervision contributed to the overall performance of employees at Bank BRI Unit Otista